Economic Results of CDD Programs : Evidence from Burkina Faso, Indonesia and the Philippines - World Bank (Washington, DC, 2012)
In Community-Driven Development (CDD) programs, communities identify, prioritize, design and execute small scale investments. While relevance and community ownership have been high, it is also crucial that these public investments meet economic feasibility criteria and generate adequate rates of return. This note summarizes the results of three recent ex-post economic analyses of CDD programs in Burkina Faso, Indonesia and the Philippines. In all cases, the overall portfolio had relatively high economic rates of return, with conservative estimates ranging from 21 to 68 percent. Quantifiable benefits of the roads, water supply systems, schools, productive projects and other investments were significant, including documented time savings, increases in local production and revenues, and savings on the cost of inputs and services, among others. In addition, a comparison of CDD implemented infrastructure projects with comparable government programs found that CDD projects consistently generated greater cost efficiency, with savings on unit costs channeled into additional community infrastructure initiatives.